Porphyrin biosynthesis in the soybean callus tissue system-XV. The effect of growth conditions - Del C. Batlle, A.M. (1975)
1. 1. Effects of various factors on chlorophyll, porphyrin and protein content, growth and on the activities of the enzymes involved in the earlier stages of tetrapyrrole synthesis, in cultured soybean cells, were studied. 2. 2. When dark-grown callus was exposed to light, it was found that the amount of porphyrins formed was not altered, but chlorophyll content as well as Succinyl CoA Synthetase (Suc.CoA-S), Aminolevulic Acid Synthetase (ALA-S), Aminolevulic Acid Dehydratase (ALA-D) and Porphobilinogenase (PBGase) activities increased. 3. 3. Addition of Aminolevulic Acid (ALA) to the medium culture, was found to stimulate porphyrin accumulation and to prevent growth; however chlorophyll content was not significantly modified. ALA-S was inhibited while both ALA-D and PBGase activities were enhanced. The action of puromycin and mitomycin added along with ALA to the media, was also studied, but neither of these inhibitors modified much the effects produced by ALA. 4. 4. Addition of Porphobilinogen (PBG), showed accumulation of uroporphyrin in the tissue; except inhibition of ALA-S, enzymes activities, protein and chlorophyll content were not modified. Evidence obtained would indicate that callus tissue was not permeable to PBG. 5. 5. Omission of iron from the culture medium, produced porphyrin accumulation and prevented growth. It has been consistently found that, the higher the content of porphyrins, the less the callus growth. Coproporphyrin was the major component of the porphyrins formed in ALA supplemented or iron deficient media. ALA-S and ALA-D were reduced under iron deficiency. 6. 6. The addition of ATP to the media, did not affect porphyrin, protein, and chlorophyll synthesis, growth or ALA-D, but Suc.CoA-S, ALA-S and PBGase activities diminished. 7. 7. Gibberelic acid produced a measurable increase of PBGase, while diminished Suc.CoA-S and ALA-S. 8. 8. Succinate increased growth and inhibited ALA-S and ALA-D. 9. 9. Carbonyl cyanide m-chlorophenyl hydrazine (CCCP), added to the medium produced accumulation of porphyrins, consequently, ALA-S was greatly inhibited and growth prevented. PBGase was also diminished. 10. 10. Coproporphyrinogenase and Decarboxylases activities were hardly detected in most experiments, and are limiting. 11. 11. The complex pattern of results obtained is discussed. © 1975.